Penanganan Anak Rawan Pendidikan di Daerah Terpencil - Sundoyo Pitomo (Jurnal Ilmu Pendidikan, 2016)
This study was an effort to seek a solution in handling the uneducated children in the context of nine-year compulsory education. It was carried out in Hargobelah, Nganjuk, East Java. Data were collected from the uneducated children, parents and formal or informal leaders by questionnaire, interview, group discussion, and documentary study. Quantitative-percentage technique was applied to analyze the data. The main solution suggested was that the children should be involved in a job training program with financial incentives and, at the same time, be participated in Package A/B programs